Effects of concrete waste on characteristics of structural fired clay bricks - Gençel, Osman; Erdoğmuş, Ertuğrul; Sütçü, Mücahit; Ören, Osman Hulusi (ELSEVIER SCI LTD, 2020)
This study focuses on evaluation of concrete waste in the production of fired clay brick. Ground concrete waste powder was replaced with the clay up to 15% by weight. Samples were shaped in the form of cylinder pellets in uniaxial press and then fired in oven at 1000 and 1100 C for 2 h. Loss on ignition, bulk density, apparent porosity, water absorption capacity, compressive strength, thermal conductivity, dilatometric, leach analysis and efflorescence analysis were done on the fired brick samples in addition to microstructure investigations. It was observed that loss on ignition, porosity and water absorption values slightly increase while compressive strength and thermal conductivity values decrease by depending on the increment in concrete waste content. Even though the brick containing 2.5% concrete waste gives better results, the bricks containing concrete waste up to 15% present compressive strength above 7 MPa which is the minimum limit. The efflorescence levels of bricks are in the slight level. It can be concluded that concrete waste can be used in the fired clay brick production.
Keywords: Construction demolition wastes; Recycling; Clay brick; Sustainability